Choose your own story: creative non-fiction about athletes attempting to qualify for the Olympics - Zamora-Solé, R.; Alcaraz, S.; Regüela, S.; Viladrich, C.; Torregrossa, M. (Qualitative Research in Sport, Exercise and Health, 2024)
The Olympics qualification phase is a taxing process for elite athletes, and despite the fact that most do not achieve their goal of qualifying for the Olympics, little is known about how they make meaning from non-qualification. This longitudinal qualitative study describes the stories of athletes preparing for the Tokyo 2020 Olympic Games in the context of the COVID-19 pandemic and interprets the athletes` meaning-making of their story of non-qualification. We conducted semi-structured interviews with seven elite athletes (a) during the COVID-19 lockdown, (b) after the COVID-19 lockdown, (c) pre-Tokyo, and (d) post-Tokyo. Results of a thematic narrative analysis are presented through creative non-fiction in the format of the `Choose your own story` genre. Two main narratives are presented: a `terminal` narrative, reflecting stories acknowledging the end of an unmade journey with no possibility of a future opportunity, and a `maybe next time` narrative, reflecting stories that acknowledge the lost opportunity while still contemplating the possibility of future qualification. This study extends previous research by providing a deeper understanding of non-event transitions and proposing a review of existing transitional models in sports. We challenge the belief that not reaching a goal constitutes failure and propose alternative narratives. Lastly, we use the innovative `Choose your own story` representation format to increase the impact of our findings on non-academic audiences.